ANALISIS EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP PENINGKATAN HASIL BELAJAR SISWA KELAS V PADA MATA PELAJARAN IPAS DI SD INPRES SARROANGIN KABUPATEN GOWA - Nurul Ismi; Andi Makkasau; Erma Suryani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted at the Elementary School Teacher Education Department, Faculty of Education, Makassar State University, under the guidance of Andi Makkasau and Erma Suryani Sahabuddin. The study aimed to analyze the application of the PBL model to V grade students of SD Inpres Sarroangin, its effectiveness in improving science learning outcomes, and the magnitude of the improvement. The quantitative method with a quasi-experimental approach (Quasi Experimental) using a Nonequivalent Control Group Design. The population was all fifth grade students, a sample of 40 students was selected by simple random sampling: class VA (experimental) and VB (control). Data were collected via observation sheets and tests (multiple choice and essay), analyzed with descriptive and inferential statistics. The results showed that the implementation of PBL in the experimental group was very good. The increase in learning outcomes was significant in the experimental group (very high category). The Independent Sample T-Test yielded a significance value of 0.001 < 0.05, thus rejecting H0 and accepting Ha, proving the significant influence of PBL on science learning outcomes. The PBL model effectively improves learning quality compared to conventional methods.